The Effectiveness of Investigations by the Satintelkam Kamneg Unit in Supporting the Disclosure of Drug Crimes in the Legal Area of the Kediri City Police - Wiratama, Akhmad Yudha (Police Studies Review, 2024)
Indonesian society still cannot escape the rampant distribution and abuse of drugs. The effects of drug addiction make it difficult for users to stop, so various methods of drug smuggling are used to secure the drug goods so that they reach the user without being discovered. Therefore, there is a need for an intelligence unit to make intelligence investigations into drug trafficking more effective as a preventive effort for the National Police to reduce the number of drug trafficking. Therefore, the aim of this research is to describe the implementation of the investigation, what obstacles were faced, as well as the effectiveness of the investigation carried out by the Kediri City Police Department, Satintelkam, Kamneg Satintelkam unit in supporting the disclosure of drug trafficking in the jurisdiction of the Kediri City Police. This research uses qualitative research methods with primary and secondary data types. The data analysis techniques used in this research are data reduction, presenting data and drawing conclusions. The first research results obtained during implementation in the field still found that many personnel made inappropriate administrative reports and did not carry out their duties according to the applicable SOPs (Implementation Operation Standards). The two obstacles experienced by Unit IV Kamneg Satintelkam in conducting investigations into drug trafficking still face many obstacles, one of which is that it is difficult to catch drug dealers because they use the Cutting System method. Third, effectiveness in conducting investigations into drug trafficking is still not effective because human resources are still very lacking, the number does not match the DSP which should be 50 according to police standards and it was also found that many budget divisions were not yet specific.